Sistim Pendukung Keputusan AHP Untuk Penataan Persyaratan Jabatan Sesuai Kompetensi Pada Direktorat Umum, SDM dan Pendidikan RSUP M. Djamil Padang Analytical Hierarchy Process as Decision Support System to Stucturing Position in Compliance with Competency in Hospital - Khairan AR Khairan AR; Hary Budiman; Helfi Agustin (PTE FTK UIN Ar-Raniry, 2017)
Realization of Activities of General, Human Resources and Education Directorate of Dr. M. Jamil Hospital to structuring position in compliance with competence requirements still low (25%), There is difficult to decide candidate whom eligible for the post in accordance with the competency, because they execute the structuring manually. One way out to reduce obstacles and to overcome this problem is using decision support system with AHP (Analytical Hierarchy Process). This method can help leaders to conduct the election candidates objectively, based multi criteria set. This research is a design engineering, built by attention to the feedback from users. Start from the planning, searching of data, analyzing, and designing using Object Oriented Design (OOD), tools to analysis by Data Flow Diagrams (DFD) , coding and subsystems that are designed last three combined into a DSS . In the construction phase, the author makes the design of the program by using the Visual Studio 6.0 with Microsoft Access database. The item is the reference of the election candidates, namely: education, rank, leadership training, office history, technical training, age, health, discipline/punishment, dedication/appreciation and courses.